Kajian Irigasi Interval 1 Hari di Musim Kemarau pada Sistem Pemanenan Air Limpasan - Chandra, Debby Shafira; Bafdal, Nurpilihan; Amaru, Kharistya (Agrotekma: Jurnal Agroteknologi dan Ilmu Pertanian, 2019)
The water resource problems in dry season at Jatinangor dry land are the imbalance between water needs and water availability. Technology that can help the farmers in dry season is by using a runoff water harvesting system for irrigation use. Irrigation interval is applied so that water use is more efficient. The purposes of this study are to calculate crop water requirement of sweet corn (Zea mays L. Saccharata Sturt) by using Cropwat 8.0 Software and to find out the use of runoff water harvesting systems on one day interval irrigation in the dry season. This research use descriptive analysis method. The results showed that based on Cropwat 8.0, the crop water requirement of sweet corn is 300,6 mm/periode and the runoff water harvesting pond can fulfill the irrigation water needs of sweet corn in the dry season with actual irrigation water requirement of 55,6 m3 on 221  m2 width of area. The productivity yield of sweet corn is 13,25  tons /ha.